Sutterby Nanofluid Flow in a Darcy–Forchheimer Permeable Medium With Chemical Reaction and Viscous Dissipation Effects: A Nonsimilar Solution - Muhammad Ramzan; Yazeed Alkhrijah; Nazia Shahmir; Ibtehal Alazman; Abdulkafi Mohammed Saeed; Muhammad Bilal; Wei Sin Koh (Journal of Mathematics)
This study looks at how an electrically conducting Sutterby nanofluid flow due to a horizontal stationary sheet behaves under the influence of the Darcy–Forchheimer effect in a porous medium. Flows across a permeable medium possess interesting applications, including environmental and biological systems like soils, bones, and tissues. Heat and mass transmissions are enriched by viscous and ohmic dissipations, radiative heat flux, and chemical reaction. A thermal convective condition is imposed on the boundary of the surface. The governing fluid model of a nonlinear system is modeled using boundary layer approximations. Further, the transformed ordinary differential equations (ODEs) are obtained via a nonsimilarity procedure up to the second level of truncation and are numerically evaluated by using the bvp4c approach. The velocity, thermal, and concentration distributions are demonstrated graphically against the pertinent factors. Quantities of engineering, such as wall heat flux, wall drag coefficient, and surface mass flux, are tabulated numerically. The outcomes depict that the Eckert number diminishes the wall heat transmission rate while the wall mass transfer rate grows for the upsurging estimates of the chemical reaction parameter. Furthermore, the Lorentz force promotes wall heat transmission and lowers the mass transfer rate. The intended model is verified against the published work using a comparison table. An excellent correlation is noted between the values in percentage of the present and the published work, substantiating its truthfulness.